Successful outcome following intralipid emulsion and plasmapheresis in a patient with profound neurologic and cardiovascular manifestations due to nortriptyline poisoning: a case report - Asma Ahmadinejad; Amir Saeed; Marzieh Davoodi (International Journal of Emergency Medicine, 2025)
Abstract Objective Tricyclic antidepressants (TCAs) are used to treat depression, but if abused or misused, they can cause poisoning, which can be fatal. The main treatment for TCA poisoning is administering sodium bicarbonate. Methods We report a 16-year-old girl diagnosed with nortriptyline poisoning with a profound neurologic and cardiovascular manifestations, successfully treated using sodium bicarbonate, intralipid emulsion, and plasmapheresis. Conclusions Plasmapheresis can be a good treatment modality for patients with TCA poisoning who do not respond well to classic treatments.